2015
DOI: 10.1002/car.2379
|View full text |Cite
|
Sign up to set email alerts
|

‘Teachers Matter’: The Impact of Mandatory Reporting on Teacher Education in Ireland

Abstract: The role of teachers in safeguarding the welfare of children is long acknowledged. However, recent research in Ireland found that the training provided to teachers on child protection issues was lacking (Buckley and McGarry, ). The frequent interactions that teachers have with children and their expertise in terms of typical child development place them in an ideal position for identifying possible signs of abuse. Yet despite this advantage, research indicates that schools fail to report a substantial proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…According to Warner and Hansen "notifying is considered a 'critical antecedent' to addressing the harm and injustices caused by child abuse and neglect. (1994, p.11) Book Chapter -India Bryce Research in the field (Taylor 1997;Taylor & Hodgkins, 2001;Kenny, 2004, Walsh & Farrell, 2008Baginsky, 2003;Bourke & Maunsell, 2015) has long argued for the inclusion of child protection 'training' in teacher education due the escalating prevalence of child abuse and neglect in Australia and globally. With the rise of statistics, comes an equally widespread intensification of responsibilities of educators, due to their placement at the forefront of detection of and response to children identified as 'at risk' or vulnerable to abuse and neglect.…”
Section: On the Front Line: The Role Of Educatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Warner and Hansen "notifying is considered a 'critical antecedent' to addressing the harm and injustices caused by child abuse and neglect. (1994, p.11) Book Chapter -India Bryce Research in the field (Taylor 1997;Taylor & Hodgkins, 2001;Kenny, 2004, Walsh & Farrell, 2008Baginsky, 2003;Bourke & Maunsell, 2015) has long argued for the inclusion of child protection 'training' in teacher education due the escalating prevalence of child abuse and neglect in Australia and globally. With the rise of statistics, comes an equally widespread intensification of responsibilities of educators, due to their placement at the forefront of detection of and response to children identified as 'at risk' or vulnerable to abuse and neglect.…”
Section: On the Front Line: The Role Of Educatorsmentioning
confidence: 99%
“…Walsh et al (2011) have identified several universities across Australia who have integrated child protection content into their courses within teacher education programs with some offering elective courses devoted to child abuse and neglect. Ireland has followed suit, with Bachelor of Education programs being lengthened and restructured to accommodate the evidence supporting the inclusion of child protection content in preservice teacher education (Bourke & Maunsell, 2015). Baginsky (2003) warns training must occur again when teachers are practicing in their field as the pressures experiences by newly qualified educators may cause their learnings to fade or be forgotten.…”
Section: Understanding and Knowledge: A Case For Preservice Teacher Ementioning
confidence: 99%
See 1 more Smart Citation
“…Mandated persons are recognised in the legislation as persons who work with children and young people and are required to report child abuse, above a defined threshold, which comes to their attention in the course of their professional or employment duties (Children First Act 2015, Government of Ireland, Irish Statute Book; Office of the Attorney General). Bourke and Maunsell () consider that teachers and schools may be regarded as the ‘arms’ and ‘eyes’ of the government, ensuring that children's rights are upheld, and that mandated reporting may be seen as important in implementing teacher and school responsibilities. Revised Children First guidelines (Department of Children and Youth Affairs, ) and the Department of Education and Skill's procedures in child protection (Department of Education and Skills, ) were published in 2017, taking account of the changes required, as a result of the publication of the 2015 Act.…”
Section: Introductionmentioning
confidence: 97%
“…All the papers above highlight some of the interesting challenges of working with children and carers in the care system. Our final paper in this issue of Child Abuse Review by Bourke and Maunsell () takes a different topic and examines the impact of mandatory reporting for teacher education in Ireland. As well as exploring mandatory reporting and the teacher role in child protection, the paper also discusses some of the implicit and explicit barriers to reporting, such as lack of staff knowledge about child abuse and neglect and implicit barriers such as an individual teacher's belief system, for example, ‘teachers’ judgments about the harm of reporting outweighing the benefits’ (p. 318).…”
mentioning
confidence: 99%